Investigation of cruise vacationers’ behavioral intention formation in the fast-growing cruise industry: the moderating impact of gender and age - Chua, Bee Lia; Lee, Sanghyeop; Hyeon, Cheol Kim; Heesup, Han (SAGE Publications, 2019)
With limited research regarding the effect of personal characteristics on the cruise decision-making process, this study attempted to investigate the interrelationships between quality factors (i.e. physical environment quality, interactional quality, and outcome quality), satisfaction, affective commitment, and behavioral intentions across gender and age groups. Our findings indicated that both interactional quality and outcome quality were significantly related to vacationer satisfaction. The mediation test revealed that both vacationer satisfaction and affective commitment played a significant mediating role in the proposed theoretical framework. The moderation test indicated that the paths from physical environment quality to vacationer satisfaction and from outcome quality to vacationer satisfaction differed significantly across males and females. In addition, our findings indicated that the link between vacationer satisfaction and affective commitment differed significantly across high and low age groups.